Deconstructing Identity: Consumerism, Masculinity, and Resistance in Fight Club - Novita Sari, Siti Maya; Englishtina, M.Pd, Dr. Inti (LINGUAMEDIA Journal, 2024)
The film Fight Club (1999), directed by David Fincher, offers a complex critique of consumerism, masculinity, and resistance. This study employs Critical Discourse Analysis (CDA) and Multimodal Discourse Analysis (MDA) to examine how the film’s language and visuals critique capitalist ideologies, challenge traditional masculinity, and explore rebellion against societal norms. The findings reveal consumerism as a force that commodifies identity, masculinity as a construct in crisis, and resistance as both rebellion and chaos. By integrating CDA and MDA, the study highlights the film’s layered critique of identity, power, and societal values, positioning Fight Club as a culturally significant text that continues to provoke critical reflection.